Der Fluch von Öl und Gas: Zur politischen Ökonomie Algeriens - Thielmann, Jörn (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2004)
Oil and gas appear as a curse, not as a blessing for Algerian economy. Instead of helping to construct an independent national economy well prepared for the post-hydrocarbon period as intended by the leaders of independent Algeria, the hydrocarbon resources hindered a sustainable development. Instead, a military regime together with the bureaucracy, both accountable to nobody, appropriates the rent generated by the petroleum and the import sector.